GOLD IN HUMIC ACIDS OF MARINE SEDIMENTS - Pashkova Y.A.; Danilova Y.A.; Vasilevskaya N.A. (My University, 1988)
Humus acids, including humic (HA) and fulvic (FA), are constant components of organic matter (OM) in continental and marine sediments. This paper reports on a study to clarify the relationship between gold and HA in marine sediments. Using the method of instrumental neutron-activation analysis, the authors investigated purified preparates of HA taken from the surface layer of ocean sediments differing in their geographic position, as well as in climatic and environmental conditions of their deposition. Study materials, methods and results are discussed.